CELL BASED DRUG DELIVERY SYSTEM THROUGH RESEALED ERYTHROCYTE - A REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Erythrocytes are biocompatible, biodegradable, possess long circulation half lives, and can be loaded with a variety of biologically active compounds using various chemical and physical methods. Erythrocytes are potential biocompatible vectors for different bioactive substances, including drugs. These can be used successfully as biological carriers of drugs, enzymes and peptides. There are currently diverse methods that permit drug encapsulation in erythrocytes with an appropriate yield. Erythrocytes loaded with drugs and other substances allow for different release rates to be obtained. Encapsulation in erythrocytes significantly changes the pharmacokinetic properties of drugs in both animals and humans, enhancing liver and spleen uptake and targeting the reticulo-endothelial system (RES). This review explains the different method of drug loading and their characterization parameters for resealed erythrocytes. This method of drug targeting is safe and effective for longer period of time and beneficial for the society.